Natural disasters, self-Insurance, and human capital investment: Evidence from Bangladesh, Ethiopia, and Malawi - Yamauchi, Futoshi; Yohannes, Yisehac; Quisumbing, Agnes R. (International Food Policy Research Institute, 2009)
This paper uses panel data from Bangladesh, Ethiopia, and Malawi to examine the impacts of disasters on dynamic human capital production. Our empirical results show that accumulation of biological human capital prior to a disaster helps children maintain investments during the post-disaster period. Biological human capital formed in early childhood (for example, good long-term nutritional status) helps insure resilience to disasters by protecting schooling investments and outcomes, even though disasters have negative impacts on the actual investments (for example, by destroying schools). In Bangladesh, children with more biological human capital are less adversely affected by flood, and the rate of investment increases with the initial human capital stock during the post-disaster recovery process. In Ethiopia and Malawi, where droughts are relatively frequent, repeated drought exposure reduces schooling investments in some cases, with larger negative impacts seen among children who embody less biological human capital. Asset holdings prior to disaster (especially intellectual human capital stock in the household) also help maintain schooling investments to at least the same degree as the stock of human capital accumulated in the children prior to the disaster. Our results suggest that as the frequency of natural disasters increases due to global warming, the insurance value of investments in child nutrition will increase. Public investments in child nutrition therefore have the potential to effectively protect long-term human capital formation among children who are vulnerable to natural disasters.